Comparative Assessment of some Physicochemical Properties of Marketed Infants Massages Oils - Khan, Obed Ullah; Sharma, Alok; Mahajan, S C (Current Research in Pharmaceutical Sciences, 2018)
Oil massage advantageous to the newborn are those related to the oil application and those related to tactile kinesthetic stimulation due to the massage. Topical oil use has been shown to improve the skin barrier function, thermoregulation and also shows to have a positive effect on growth. Present work was conducted to standardize the selected five marketed infant massage oils for their physicochemical parameters, i.e. color, odor, pH, specific gravity, acid value, peroxide value and saponification value. The findings of the study showed that the infant massage oils were complies the requirements for physicochemical parameters as prescribed in standard text.